Formação docente em tempos de pandemia ano (2020) no contexto da educação do campo em Mossoró-RN - Gurgel, Aline Kartienne Lima de Morais (2021)
The present work deals with teacher education in times of pandemic, taking a look at this reality in rural education at UFERSA. The general objective is to analyze the adop-tion of remote/supplementary education in the semester 2020.1 at UFERSA from the perspective of online teaching of teachers and students who work in the Interdiscipli-nary Degree in Rural Education (Mossoró-RN). Throughout the research, some specific objectives were outlined seeking to: 1) understand the contextualization of the move-ment for an education in the countryside 2) discuss the Technologies Associated with Education 3) analyze the context of the remote classes of the Interdisciplinary Degree in Field Education UFERSA (Mossoró-RN) 4) Identify the level of training of students in the environment of academic education permeated by Information and Communication Technology (ICT) in the context of the current pandemic. The problematization is sup-ported by the aspects that involve the reality of teachers and students who experience a training process mediated by the use of technologies in the midst of a pandemic caused by Covid-19. We started from a qualitative and quantitative approach using question-naires composed, respectively, by a Likert scale and open questions. Quantitative data were analyzed using classical statistics. Qualitative data were approached according to content analysis, with categories that emerged from the reading of the answers based on Bardin's content analysis (1977). Theoretically, the discussion is supported by the con-ceptions of different authors starting with Souza (2016), Amora et. al (2011),Pocho et al. .(2014), Sampaio et al (2014),Leal and Mengarelli (2018), Arroyo, Caldart and Mo-lina (2011-2017,2018), Lima and Silva (2011),Costa (2014)). Imbernón (2006); Pimenta (2006). Fazenda et al (2014), among others. For Methodology: Gil (2008), Severino (2007). For the teacher, a participant in the research, some pedagogical requirements are necessary to establish a new conception of learning, articulation and production of ac-tivities inherent to teaching, his speech shows that even for a professional with experi-ence, high level of education, improvement course to work with digital tools of infor-mation and communication, there are still many difficulties, among them: Practical ex-perience with remote classes, use of technological tools, emotional factors, engagement of the family and of training spaces, more autonomy, protagonism, involvement and emotional balance on the part of the students, confinement and social distance. We also found that remote classes cause anxiety, insecurity, and affect the students' initial for-mation at some point. The results indicate that for the students the difficulties in access-ing the classes, emotional factors, internet that is not always of good quality, harm their performance in remote classes in times of pandemic, and that they consider themselves participative in the classes and that they receive average feedback by the teacher